PERENCANAAN PEMBANGKIT LISTRIK TENAGA SURYA SEBAGAI SUPLAI DAYA POMPA AIR SUBMERSIBLE INOTO 2 HP DI DUSUN LERAN - Ogik Azis Bukhori; I Nyoman Setiawan; I Wayan Arta Wijaya (Jurnal SPEKTRUM, 2021)
The Water Pump System in Leran Hamlet is intended to meet the water needs of thecommunity, the pump used is an INOTO 2 HP submersible water pump driven by a 1 phaseelectric motor. This study designing grid-tied solar system based on the water pump powerwhich has simulated with PVSyst. In this study, the water pump is projected to lift water from theground with a volume of 1,328 m/month according to customer water usage. The Solar PowerPlant system uses 10 unit of 335 Wp Risen RSM72-6-335P solar modules and an 4 kW inverterSolis 1P4K-4G. The simulation results show that the annual energy production of PLTS is 4.194MWh/year with solar fraction 1.28 which means Solar Power Plant is able to meet the energyneeds of water pump. The investment analysis resulted in Net Present Value isRp.145,867,228, Profitability Index is 3.6 and Discounted Payback Period is 4.3 years whichindicates that the investment is feasible.